2021
DOI: 10.1101/2021.10.04.462661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain networks in human conscious visual perception

Abstract: Consciousness is not explained by a single mechanism, rather it involves multiple specialized neural systems overlapping in space and time. We hypothesize that synergistic, large-scale subcortical and cortical attention and signal processing networks encode conscious experiences. To identify brain activity in conscious perception without overt report, we classified visual stimuli as perceived or not using eye measurements. Report-independent event-related potentials and functional magnetic resonance imaging (f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 58 publications
5
8
0
Order By: Relevance
“…By using this task in conjunction with large scale recordings from patients undergoing intracranial electroencephalography and through measuring neural activity by quantifying power in broadband gamma frequencies, we showed that a rapid progression of neural events closely followed a consciously perceived auditory stimulus; and that the scope of events associated with not-perceived stimuli is limited almost entirely to primary and other nearby early auditory cortex. Our findings expand the switch-and-wave model previously put forward by Herman, Smith 4 , and support more recent work done conducted with scalp EEG, fMRI and pupillometry 5 by adding two additional components: detect and pulse 47, 52, 56 . In this expanded model 6 , consciously perceived stimuli elicit a series of neural events: (1) detect : an initial activation of early sensory and other areas critical in the detection of incoming sensory stimuli (such as the frontal eye fields); (2) a pulse of activity originating from subcortical regions such as the thalamus; (3) a monophasic wave of activity that propagates from sensory regions to higher-order and association cortical regions and (4) the switch ing off of default-mode related regions.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…By using this task in conjunction with large scale recordings from patients undergoing intracranial electroencephalography and through measuring neural activity by quantifying power in broadband gamma frequencies, we showed that a rapid progression of neural events closely followed a consciously perceived auditory stimulus; and that the scope of events associated with not-perceived stimuli is limited almost entirely to primary and other nearby early auditory cortex. Our findings expand the switch-and-wave model previously put forward by Herman, Smith 4 , and support more recent work done conducted with scalp EEG, fMRI and pupillometry 5 by adding two additional components: detect and pulse 47, 52, 56 . In this expanded model 6 , consciously perceived stimuli elicit a series of neural events: (1) detect : an initial activation of early sensory and other areas critical in the detection of incoming sensory stimuli (such as the frontal eye fields); (2) a pulse of activity originating from subcortical regions such as the thalamus; (3) a monophasic wave of activity that propagates from sensory regions to higher-order and association cortical regions and (4) the switch ing off of default-mode related regions.…”
Section: Discussionsupporting
confidence: 89%
“…Although the onset of this early sensory activity was consistent with the visual version of the task 45 , the dynamics of activation differed. Whereas in the visual task, gamma power in the primary visual areas showed an increase (<200 ms), followed by a decrease below baseline (200–600 ms), followed by a secondary increase (>600 ms), thus leading us to include the primary visual areas as a component of the ‘switch’, here we saw a sustained increase in early auditory regions.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…66 In addition, although EEG and fMRI no-report paradigms have been previously used, the high spatial and temporal precision of intracranial recordings could provide valuable insights into the precise timing of conscious processing in the brain, including in the prefrontal cortex. 35,63,67 Specifically, methods with precise temporal resolution may help researchers differentiate between frontal activation associated with motor planning and execution, compared with other post-perceptual processes like decision-making, classification, memory, etc. Finally, other analysis methods, specifically representational similarity analysis, should be incorporated into no-report paradigms.…”
Section: Future Directionsmentioning
confidence: 99%